simplify :- (2x-5y)³+(2x+5y)³
Answers
Answered by
19
✠EXPLANATION:-
✠ Given to simplify:-
(2x-5y)³+(2x+5y)³
✠ Answer :-
16x³ + 300xy²
✠Solution:-
As we know that ,
⟶ (a+b)³ = a³+ b³ + 3ab(a+b)
⟶ (a-b)³ = a³ -b³ -3ab(a-b)
So, by using these formulae we can expand the following and can simplify it
⟶ (2x +5y)³ +(2x-5y)³
⟶ (2x)³ + (5y)³ +3(2x)(5y)[2x+5y] + (2x)³ -(5y)³ -3(2x)(5y) [2x-5y]
⟶ 8x³ + 125y³ + 30xy[2x+5y] + 8x³ - 125y³ - 30xy[2x-5y]
⟶ 8x³ +125y³ + 60x²y + 150xy²+ 8x³ - 125y³ - 60x²y + 150xy²
✠Keep like terms together
⟶ 8x³ + 8x³ +60x²y -60x²y + 150xy² + 150xy² + 125y³ - 125y³
⟶ 16x³ + 300xy²
So, the value of (2x-5y)³+(2x+5y)³ is 16x³ + 300x
✠Know more :-
⟶(a+ b)² = a² + b² + 2ab
⟶( a - b )² = a² + b² - 2ab
⟶( a + b )² + ( a - b)² = 2a² + 2b²
⟶( a + b )² - ( a - b)² = 4ab
⟶( a + b + c )² = a² + b² + c² + 2ab + 2bc + 2ca
⟶a² + b² = ( a + b)² - 2ab
⟶(a+b)(a-b) = a²-b²
⟶ If a + b + c = 0 then a³ + b³ + c³ = 3abc
Answered by
0
This is your answer. Hope it will help you a lot.
Attachments:
![](https://hi-static.z-dn.net/files/d4d/c354d14831181d6024c6200ecf6a8243.jpg)
Similar questions